Hidrotiolação regio e estereosseletiva de sistemas diínos: síntese e reatividade de (Z)-tioeninos - Welter, Luiz Eduardo (2022)
Sulfur compounds are important building blocks in Organic Chemistry. The class of vinyl sulfides stands out for its versatility and applicability in the synthesis of new structures. Due to the relevance of these compounds, we intend to find a new methodology for the regio and stereoselective synthesis of (Z)-thioenynes a direct hydrothiolation of conjugated 1,3-diynes promoted by lithium thiolate. A systematic study of the reaction conditions revealed that the presence of ethanol played an essential role in obtaining (Z)-thioenyne compounds with yields between 50 and 93%. The standard reaction conditions were compatible with different functional groups in the substrates, such as alkyl and propargyl alcohols, as well as aryl variations with electron-withdrawing and electron-donating groups. Based on the data obtained, we verified that in this hydrothiolation reaction, lithium thiolate, formed by the reaction n-butyllithium with elemental sulfur, promotes an anti-pathway addition to carbon-carbon triple bond and the concomitant trapping of hydrogen from ethanol by the formed vinyl anion. The (Z)-thioenynes obtained by the described method proved to be versatile substrates for the synthesis of functionalized thiophenes through copper-catalyzed electrophilic cyclization reactions with diphenyl diselenide.